Hybrid fuzzy-GMC control of gas-phase propylene copolymerization in fluidized bed reactors - Nazratul Fareha Salahuddin (Elsevier, 2021)
A modified two-phase model is presented to describe the process of gas phase propylene and ethylene copolymerization in a fluidized bed reactor (FBR). Entrainment of solid particles in the FBR is considered in the model, as an improvement to the original two-phase model. Non-linearity of this process makes it difficult to control only by the conventional controllers, such as PID. A hybrid control strategy (a simple designed fuzzy logic controller (FLC) integrated with generic model control (GMC)) was designed to control the reactor temperature. This advanced control system was compared with the GMC and conventional PID controllers. The simulation results showed that the hybrid controller (Fuzzy-GMC) performs better than either GMC or PID for set point tracking and disturbance rejection with very low overshoot as well as fast and stable response. The hybrid controller movement was also very stable and fast in terms of both servo and regulatory control, suitable for robust application.